(untitled) (Asian Journal of Agriculture, 2017)
Abstract. Sheriff O, Alemayehu K. 2017. Review: Genetic diversity studies using microsatellite markers and their contribution in supporting sustainable sheep breeding programs. Asian J Agric 1: 46-51. Microsatellites have been widely accepted and employed as useful molecular markers for measuring genetic diversity and divergence within and among populations. The various parameters developed so far to measure genetic diversity within and among populations are observed and expected heterozygosity (Ho and He), the mean number of alleles per locus (MNA), polymorphic information content (PIC), genetic distance and phylogenetic or tree building approach. The objective of this review was therefore to quantify the genetic diversity studies of domestic sheep populations using microsatellite markers and their contribution in supporting sustainable sheep breeding programs. From the review, it is possible to see that there were high population genetic variations in all the studied sheep populations, poor levels of population differentiation and high levels of inbreeding. On the other hand, low estimates of heterozygosity and mean number of alleles and employing only few and weak markers were observed in some of the studies. The gaps observed in the previous genetic diversity studies of the sheep populations may demand further works to reveal more information on the population structures and to start appropriate and sustainable breeding programs.